Polyamines modify the nitrosative status of salt stressed plants - Tanou, Georgia; Ziogas, Vasileios; Christou, Anastasis; Diamantidis, Grigorios; Fotopoulos, Vasileios; Molassiotis, Athanassios (My University, 2011)
Although there is accumulating evidence that polyamines are involved in the response of plants to both salinity and nitrosative stress, their role is not yet fully understood. The present study attempts to examine the effects of hydroponic root treatments with putrescine (Put, 1 mM), spermidine (Spd, 1mM) and spermine (Spm, 1mM) on nitrosative homeostasis in leaves of citrus plants (Citrus aurantium L.) exposed to 100 mM NaCI for 15 d. Nitric oxide (NO) steady-state levels and DAF-2DA-derived fluorescence were stimulated by NaCI treatment and especially by the application of polyamines in the salt-treated plants. Transcriptional analysis showed that the expression of several genes encoding proteins associated with NO biosynthesis, including AOX, XO, GSNO, NOS, NiR and NR, is regulated by polyamine application. In addition, S-nitrosoglutathione reductase (GSNOR) activity was suppressed in plants treated with Put and Spd. The profile of tyrosine-nitrated proteins was diminished by the application of polyamines. The characterization of nitroproteome by mass fingerprinting revealed several protein targets which are involved mainly in photosynthesis, disease/defense, energy and protein destination/storage. These data strongly support a function of polyamines in modulating the nitrosative status upon salt stress.